The Solid-State Synthesis of BiOIO3 Nanoplates with Boosted Photocatalytic Degradation Ability for Organic Contaminants - Jia Li; Jing Xie; Xiaojing Zhang; Enhui Lu; Yali Cao (Molecules, 2023)
BiOIO3 exhibits excellent oxidation capacity in the photocatalytic degradation of contaminants thanks to its unique polarized electric and internal electrostatic field. However, the synthetic method of BiOIO3 nanomaterials is mainly focused on hydrothermal technology, owing to its high energy consumption and time-consuming nature. In this work, a BiOIO3 nanosheet was prepared by a simple solid-state chemical reaction, which was identified by XRD, EDS, XPS, and HRTEM. Benefiting from the strong oxidation ability of the valence band maximum, the distinctive layer structure, and the promoted generation of ·O2−, the BiOIO3 nanosheet exhibits excellent photo-degradation activity for methyl orange (MO) and its apparent rate constant is 0.2179 min−1, which is about 3.02, 8.60, and 10.26 times higher than that of P25, BiOCl, and Bi2O2CO3, respectively. Interestingly, the BiOIO3 nanosheet also has good photocatalytic degradation performance for phenolic compounds; in particular, the degradation rate of BPA can reach 96.5% after 16 min, mainly due to hydroxylation reaction.